Assessment of CO2 enrichment mechanism in integrated coal gasification fuel cell combined cycle system with carbon capture - Wang, Yuan; Wu, Chengru; Wang, Yang; Yang, Zhibin; Du, Qing; Jiao, Kui (Frontiers in Energy Research, 2023)
The present research proposes innovative multi-physics coupled model of different configurations of an integrated coal gasification fuel cell combined cycle (IGFC) system employing Solid Oxide Electrolytic Cell (SOEC) for CO2 capture. Full-system simulation is carried out to examine the efficiency and economic performance. The model incorporates a Solid Oxide Fuel Cell (SOFC), a SOEC, a gas turbine (GT), and multiple recirculation loops operated by two ejectors. The results reveal that compared with traditional power plants, the proposed IGFC system equipped with SOEC can reduce CO2 emission by almost 80%, and operates environmentally beneficial. The economic performance of the system varies greatly depending on the design parameters implemented. The CO2 enrichment phenomenon by SOFC and capture measures of CO2 by SOEC are simultaneously analyzed. In addition, parametric analysis is performed to evaluate the coupling influence of multiple operating parameters on the IGFC system. Recirculation ratios of 0.75 with four times of recirculations are found to be the optimal conditions for both SOFC fuel electrode and SOEC air electrode aimed at getting to the highest power generation efficiency and total CO2 capture rate of the system. After systematic optimization of the design parameters, the electrical efficiency and CO2 capture rate of the proposed system could achieve 68.47% and 87.88%, respectively, which are about 20% and 60% greater than those of traditional power plants. Furthermore, after optimizing the control strategy, the fuel utilization rate of the system increases from 63.09% to 83.40%.